Examining the Interactions Between Expectations and tDCS Effects on Motor and Cognitive Performance - Rabipour, Sheida; Vidjen, Petar Sefik; Remaud, Anthony; Davidson, Patrick S. R.; Tremblay, François (Frontiers in Neuroscience, 2019)
Background: Transcranial direct current stimulation (tDCS), increasingly promoted for motor and cognitive enhancement, remains shrouded in controversy. Despite a growing literature and commercial market, tDCS effectiveness remains questionable. Notably, studies rarely examine factors such as expectations of outcomes, which may influence tDCS response through placebo-like effects. We sought to determine whether expectations could influence responses to a tDCS intervention. Methods: We recruited 121 naive young adults 18-34 years of age (M=21.14, SD=3.58; 88 women). We evaluated expectations of tDCS as well as motor and cognitive performance at three times: i) at baseline; ii) after being primed to have High or Low expectations of outcomes; and iii) after a single session of sham-controlled anodal tDCS over the left or right motor cortex. Before and after stimulation, participants performed tasks measuring motor dexterity, response time, and response inhibition. Results: Repeated measures ANOVA revealed that participants had varying, largely uncertain, expectations regarding tDCS effectiveness at baseline. Expectation ratings significantly increased or decreased in response to High or Low priming, respectively, and decreased following the intervention. Response times and accuracy on motor and cognitive measures were largely unaffected by expectation or stimulation conditions. Overall, our analysis revealed no effect attributable to baseline expectations, belief of group assignment, or experimental condition on behavioral outcomes. Subjective experience did not differ based on expectation or stimulation condition. Conclusions: Our results question the efficacy of tDCS as a performance enhancer, supporting recent criticisms of this technique and highlighting the need for further investigations regarding tDCS effects. Researchers and clinicians should consider the potential effects of expectations when designing tDCS interventions and interpreting outcomes to determine whether such methods are truly effective.